Pengaruh Return On Asset, Sales Growth, Karakteristik Eksekutif dan Pofitabilitas Terhadap Tax Avoidance - Muhammad Ikhlasul; Dirvi Surya Abbas; Hamdani, Hamdani; Samino Hendrianto (Pusat Riset dan Inovasi Nasional, 2022)
ABSTRACT The purpose of this study was to determine the effect of Return On Assets, Sales Growth, Executive Characteristics and Profitalities on Tax Avoidance in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 7 years, namely the 2013-2021 period.The population of this study includes all consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 7 years of the company. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis.The results show that return on assets has a positive effect on tax avoidance, sales growth and executive characteristics have a negative effect on tax avoidance together.